Building Stones of Canada's Federal Parliament Buildings - Lawrence, D. (Geoscience Canada, 2001)
Summary The building stones used in the Ottawa Parliament Buildings were mined from numerous quarries in Canada, United States, and several European nations.They were cut, placed and carved according to exacting procedures using the most up-to-date technology of the time. Construction of the rebuilt Centre Block, the focus of this article, was a protracted affair, interrupted by the demands of the1914-1918 Great War. Exterior stone ofthe Parliament Buildings has endured the ravages of weather, fire, seismic shaking and pollution. Recently, great effort and expense have been devoted to the restoration of the masonry elements of all of the buildings to ensure the continued viability of this National Historic Site.The role of the geologist, critical in the initial evaluation and selection of the building stone, was largely ignored until recently. Building restoration of late has also restored the role of the geologist, with the requirement to understand the complex reactions of the building stone to the environment and its neighbouring masonry elements, and in the quest to find suitable replacement stone.